New antimycobacterial S-alkylisothiosemicarbazones - Waisser, K; Heinisch, L; Slosárek, M; Janota, J (Folia microbiologica, 2005)
In connection with a systematic study of antimycobacterial agents against potentially pathogenic strains the series of 12 S-alkylisothiosemicarbazones was evaluated for in vitro antimycobacterial activity against Mycobacterium tuberculosis, M. kansasii, M. fortuitum, two strains of M. intracellulare and three strains of M. avium. Quinoline-4-carbaldehyde-S-hexyl-isothiohydrazone was found to be more active against potentially pathogenic strains than isoniazide.
Keywords: Mycobacterium kansasii; thiosemikarbazony; Aldehydes; Thiosemicarbazones; Microbial Sensitivity Tests; Mycobacterium tuberculosis; aldehydy; Mycobacterium fortuitum; netuberkulózní mykobakterie; mikrobiální testy citlivosti; antibakteriální látky; Anti-Bacterial Agents; Mycobacterium avium komplex; Nontuberculous Mycobacteria; Mycobacterium avium; Mycobacterium avium Complex